Investment in education, the way for Romania to succeed - Emilia Ungureanu; Felix-Constantin Burcea (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2010)
The new economical approach highlights more and more the importance of humancapital. Presented as giving a big contribution to the social wealth, the accent is putted overthe fact that the investment in this direction is one of the most important.Under these circumstances we are analyzing the particular case of Romania as a developingcountry, the investment made in education and the effects of the global crisis in this field.